The pentateuch ; v. 3 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Martin, James (Grand Rapids, MI Eerdmans)
Contents : v. 3 : the fourth book of Moses (Numbers) ; the fifth book of Moses (Deuteronomy). Includes bibliographical references.
Keywords: Bible. O.T. Pentateuch -- commentaries